2011
DOI: 10.3399/bjgp11x549009
|View full text |Cite
|
Sign up to set email alerts
|

Bereavement care in primary care: a systematic literature review and narrative synthesis

Abstract: BackgroundOver half a million people die in Britain each year and, on average, a GP will have 20 patients die annually. Bereavement is associated with significant morbidity and mortality, but the research evidence on which GPs and district nurses can base their practice is limited. AimTo review the existing literature concerning how GPs and district nurses think they should care for patients who are bereaved and how they do care for them. DesignSystematic literature review. MethodSearches of AMED, BNI, CINAHL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 21 publications
0
36
0
7
Order By: Relevance
“…GPs and community nurses view bereavement care as an important and satisfying aspect of their job. However, they feel underprepared and practice varies markedly across services (Nagraj & Barclay, 2011). Accordingly, the true cost of bereavement in terms of consultations at Scottish GP practices may be more substantial.…”
Section: Discussionmentioning
confidence: 99%
“…GPs and community nurses view bereavement care as an important and satisfying aspect of their job. However, they feel underprepared and practice varies markedly across services (Nagraj & Barclay, 2011). Accordingly, the true cost of bereavement in terms of consultations at Scottish GP practices may be more substantial.…”
Section: Discussionmentioning
confidence: 99%
“…Current understandings on grief care derive mostly from primary care (Birtwistle et al . , Nagraj & Barclay ), hospital care (Warren ) or hospices (Foliart et al . , Field et al .…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with theories that participation of and interactions among providers of a variety of backgrounds can enhance care, [31][32][33] research has demonstrated that social worker and volunteer involvement, and interdisciplinary collaboration more broadly, are associated with better quality of care for people in hospice. 22,34,35 Training requirements have also been associated with quality of bereavement care provision specifically, 36 but these associations have not been adequately studied for hospice bereavement care. As previous findings and existing theory predicted, it was hypothesized that lengthier training requirements, interdisciplinary team attendance from a large range of providers, and a lower ratio of volunteer hours to number of individuals in hospice would be associated with higher likelihood of conducting CG and depression screening and referral.…”
mentioning
confidence: 99%